Technique development of attractant test for Chrysomya bezziana in laboratory and semi-field conditions - April H Wardhana; Sukarsih . (Jurnal Ilmu Ternak dan Veteriner, 2004)
Swormlure (SL-2), synthetic attractant for the New World Screwworm Fly (NWSF), Cochliomya hominivorax, have been developed and used in the America. The effectiveness of swormlure in attracting the Old World Screwworm Fly (OWSF), Chrysomya bezziana is not well defined. The aim of the study was to provide suitable condition of the attractant in trapping the higher number at the OWSF in laboratory (cage assay) and semi-field (room assay) conditions. The cage assay to screen responses olfactory stimuli of OWSF was developed to asses the fly responses to lights, exhaust fan (on or off), the flies’ physiological status and whether there was any bias between cages or trap positions. Modifications were made to provide suitable physical and environmental conditions for candidate attractant. These included darkening all windows with paper, the construction of support for the fly cages and installation of additional lights centred above the fly cages. The room assay was used as an intermediate step between the cage assay and the field experiment. The number of entered flies into the trap indicated flies respond to SL-2. The data of cage assay was analysed by ANOVA and data of room assay was analysed by T test (5%). The results showed that standard experimental conditions for the cage assay: two lights above the cages on and the central lights off, covering fluorescent lights with oil paper, the jar trap positions on the centre line parallel to the lights and exhaust fan was turned off (no air flow) during the session but was turned on in between sessions to reduce the odour from SL-2 in laboratory (p>0.05). The standard experimental conditions for the room assay used four fluorescents tubes, exhaust fan turned off during the replicates but turned on after replicated 3 and 6 for 15 minutes. Yellow half-size sticky was used as standard target (p>0.05).   Key words: Swormlure, SL-2, attractant, Chrysomya bezziana